The level of the quality of life in the city and its monitoring. - Wolniak, Radosław; Jonek-Kowalska, Izabela (Innovation: The European Journal of Social Sciences, 2021)
The publication presents the results of analyses regarding the measurement of the quality of life of urban residents in Poland and the methods used for this monitoring. The purpose of the research was to determine whether continuous monitoring of the quality of life in the city helps to improve its level. The results of the conducted research support all three hypothesis. On the basis of our analysis we observed that implementing the ISO 37120 standard helps to improve the quality of life in the city. The observed phenomenon is particularly important when developing the concept of a Smart City. Nowadays, digitisation of life and the possibility of collecting, easier than before, data on various aspects of the city's operation is the main driving force behind the implementation of the Smart Cities concept. The smarter a city becomes, the more and easier it collects data on the quality of life.